Representaciones sociales del insulto entre estudiantes de la Institución Educativa Mariscal Cáceres en Ayacucho, Perú - Gutiérrez Martínez, Juan Benigno (2023)
The main objective of this research was to analyze the social representations on the acts of verbal insults among third grade high school students at the Mariscal Caceres Educational Institution, located in the district of Ayacucho in Peru. The empirical information was obtained through the survey and its respective instrument: the perception and valuation questionnaire which included closed and open questions, that was applied to a total of 64 students, both male and female. The results reveal that 95 % of the students surveyed stated that they had been victims of verbal insults. Despite this, they define and categorize such acts as a simple “lack of respect”, followed, to a lesser extent, by other categories: violence, aggression and even considered as something normal. To cope with this situation, students take various decisions and actions: complaining to their parents and teachers, responding with physical violence, exchanging insults, remaining silent or simply letting themselves be carried away by the situation. Therefore, students are not mere spectators or passive agents in the face of the problem they experience but possess and deploy their capacity for agency.